The Role and Position of Students at the University of Maribor - Hrast, Nomi; Majcen, Žiga; Slaček, Pina; Lah, Luka; Tepić, Maša; Hauc, Ema (50 let Univerze v Mariboru: Pol stoletja znanja in raziskovanja, 2025)
Students are a key part of the University of Maribor, which would not exist in principle without them. Over the decades, the number of students has grown and today there are more than 15,000 students studying at the University of Maribor. Their involvement in activities to represent student interests and develop extra-curricular activities at the local and national level has been ever-present. The latter plays an important role as it contributes to the development of competences, social networks and the quality of student life. Student representation, particularly through student councils, ensures the representation of students' rights and interests and enables their participation in decision-making. The University of Maribor enables students to participate in governance, as representatives are present in all decision-making bodies, including the Vice-Rector and the Vice-Deans for Student Affairs. Students have thus actively co-shaped the University and contributed to its current position in Slovenia and abroad, to its internationalisation and to its broader social development.